Preparation Of Nahw and Sharf Teaching Facilities and Technologies for Basic Level: اعداد وسائل وتكنولوجية تعليم القواعد النحوية والصرفية للمستوى الابتدائية - M. Hari Zakiyudin (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2021)
One of the successes in the world of education is the use of appropriate and enjoyable learning media for students in the classroom; many primary school students often have difficulty learning Arabic because they do not understand the meaning of each word explained by the teacher. This study aims to describe the preparation of media and learning technology grammar (nahwu) and morphology (shorf) and examples of models for the primary school level. The researcher used a qualitative approach to obtain the desired results as research material. The results of the study showed that in preparing the Learning media, teachers must pay attention to five things represented in (1) determining the educational goals to be achieved accurately, (2) knowing the characteristics of the target group and taking them into account (3) knowing, and (5) evaluation to choose the suitable method. Then examples of learning media such as pictures or pieces of words, as well as speakers or videos for schools that are supported by electronic devices, and natural learning (outside the classroom) when students feel bored with education in the school and need a new environment. من المعلوم أن من نجاح التعليم استخدام وسائل التعليم المناسبة والمريحة لدى الطلاب داخل الفصل، ويهدف هذا البحث في وصف اعداد وسائل وتكنولجية تعليم القواعد النحوية والصرفية ونموذجها للمستوى الابتدائية. ونهج الباحث إلى المنهج الكيفي ليحصل على نتيجة يريد أن يضع البحث نصب عينيه، وأشارت النتيجة بأن المدرس عندما يعد الوسائل التعليمية لابد من الإهتمام عن الأمور الخمسة تتمثل في (١) تحديد الأهداف التعليمية التي تحققها الوسيلة بدقة (٢) ومعرفة خصائص الفئة المستهدفة ومراعاتها (٣) ومعرفة بالمنهج المدرسي ومدى ارتباط هذه الوسيلة وتكاملها من المنهج (٤) وتجربة الوسيلة قبل استخدامها (٥) وتقويم الوسيلة حتى يحصل على اختيار الوسائل التعليمية المناسبة.